Prevalence of calcaneal spur among foot and ankle patients at the Cape Coast Teaching Hospital, Ghana - Fiagbedzi, Emmanuel; Ofori, Nana; Amlalo, Jeffrey Gameli (Faculty of Medicine Universitas Indonesia, 2024)
BACKGROUND A calcaneal spur is a bony protrusion that grows from the calcaneus. This study aimed to estimate the prevalence of calcaneal spurs and associated risk variables (age, gender, and type) in patients undergoing foot and ankle X-ray examinations at the Cape Coast Teaching Hospital. METHODS A retrospective cross-sectional approach and non-probability purposive sampling were used to analyze radiographic reports. A total of 323 radiographic reports from patients undergoing ankle and foot X-ray examinations between July 2020 and July 2023 were selected from 1,690 radiographs and analyzed using Microsoft Excel 2019 and SPSS software version 26.0. RESULTS The overall prevalence was 34.7% (112/323), with 112 cases indicating calcaneal spurs. Of the patients, 72 (64.3%) were females. Among the cases, 53 (47.3%) were plantar spurs, 40 (35.7%) were dorsal spurs, and 19 (17.0%) exhibited both types. The highest prevalence was found in the 51–60 age group, representing 30 (26.8%) cases. Age was found to have a significant association with calcaneal spur development (p = 0.044). CONCLUSIONS Both plantar and dorsal calcaneal spurs were significantly associated with age, with the 51–60 age group at higher risk.